Galileo infrared imaging spectroscopy measurements at venus. - Carlson, R; Baines, K; Encrenaz, T; Taylor, F; Drossart, P; Kamp, L; Pollack, J; Lellouch, E; Collard, A; Calcutt, S; Grinspoon, D; Weissman, P; et al. (1991)
During the 1990 Galileo Venus flyby, the Near Infaied Mapping Spectrometer investigated the night-side atmosphere of Venus in the spectral range 0.7 to 5.2 micrometers. Multispectral images at high spatial resolution indicate substanmial cloud opacity variations in the lower cloud levels, centered at 50 kilometers altitude. Zonal and meridional winds were derived for this level and are consistent with motion of the upper branch of a Hadley cell. Northern and southern hemisphere clouds appear to be markedly different. Spectral profiles were used to derive lower atmosphere abundances of water vapor and other species.